PENGEMBANGAN SUMBER DAYA MANUSIA DALAM MENINGKATKAN KUALITAS PENDIDIKAN DI SEKOLAH DASAR (STUDI KASUS DI SD ISLAM PERMATA MOJOSARI KAB. MOJOKERTO) - Miftakul Janah; Satunggale Kurniawan; Muhammad Afifi Rahman (Multidisciplinary Indonesian Center Journal (MICJO), 2024)
The quality of education of a nation is largely determined by the quality of human resources especially educators. Therefore, it is a necessity for every educational institution to improve the quality of teaching staff. The purpose of study are to find out how the development of human resources process from teacher staff to improve the quality education and how the supporting and inhibiting factors to impove the quality education at SD Islam Permata Mojosari. This study used a qualitative approach to the type of case study, which research is carried out at SD Islam Permata Mojosari. Data collection is done using techniques: interviews, observation, and documentation. While the data obtained were analyzed through several stages namely: Condensation, data display, and verification of conclusions as well as checking the validity of the data. The process of developing human resources educators has been going well, but there are still shortages here and there both in terms of implementation and evaluation of the results of the development.